Digital Literacy Efforts to Prevent Pornography and Sexsual Violence Among Gen Alpha in Kota Bengkulu - Damayanti, Poppi; Yuhaswita, Yuhaswita (Jurnal Ilmiah Syi'ar, 2025)
The digital world for the Gen Alpha group today has become a challenge that must be considered by all parties, especially the openness of information without limits. Therefore, this study aims to provide an overview of education as a reflection of achieving awareness so that it can filter the information needed. Using the ABCD method, the author developed an approach in the field to raise awareness through digital literacy. So the results of the study show: Discovery (Finding Strength), taking information about the map of students' strengths as Gen Alpha facing the current digital world Dream (Building Dreams) Next, students together with facilitators design what desires they want to achieve with the current condition of assets. Design (Planning Actions) From the previous mapping, it is continued with action planning or preparation of RTL. Define (Gathering Strength) The PKM UIN FAS team collaborated with students of SMP N 2 Bengkulu City to compile a pocket book containing terms in Online Gender-Based Violence/KBGO to be used as a guideline by students to avoid pornography and sexual violence. Destiny (Ensuring Implementation) After the FGD is carried out, the PKM UIN FAS Bengkulu team will continue the discussion and preparation of a pocket book that is easy to understand and acceptable to students.